Environmental options and technological innovation: An evolutionary game model - Angelo Antoci; Simone Borghesi; Marcello Galeotti (Fondazione Eni Enrico Mattei (FEEM), 2009)
This paper analyses the effects on economic agents' behaviour of an innovative environmental protection mechanism that the Public Administration of a tourist region may adopt to attract visitors while protecting the environment. On the one hand, the Public Administration sells to the tourists an environmental call option that gives them the possibility of being (partially or totally) reimbursed if the environmental quality in the region turns out to be below a given threshold level. On the other hand, it offers the firms that adopt an innovative, non-polluting technology an environmental put option that allows them to get a reimbursement for the additional costs imposed by the new technology if the environmental quality is above the threshold level. The aim of the paper is to study the dynamics that arise with this financial mechanism from the interaction between the economic agents and the Public Administration in an evolutionary game context.
Keywords: C73; D62; G10; O30; Q28; 330; Environmental Bonds; Call and Put Options; Technological Innvoation; Evolutionary Dynamics